Climate Change Adaptation, Resilience and Hazards - Leal Filho, Walter; Musa, Haruna; Cavan, Gina.; O'Hare, Paul.; Seixas, Julia; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book analyses the links between climate change adaptation, resilience and the impacts of hazards. The contributors cover topics such as climate change adaptation in coastal zones, the evaluation of community land models, climate change considerations in public health and water resource management, as well as conceptual frameworks for understanding vulnerabilities to extreme climate events. The book focuses on a variety of concrete projects, initiatives and strategies currently being implemented across the world. It also presents case studies, trends, data and projects that illustrate how cities, communities and regions have been striving to achieve resilience and have handled hazards.
Preface -- Part I: Climate Change Adaptation Practices -- Part II: Fostering Resilience and Handling Hazards.
Keywords: Environmental economics; Geology; Climate Change/Climate Change Impacts; Climate Change Management and Policy; Natural Hazards